Intimidación escolar en estudiantes de pregrado de odontología en una universidad Colombiana (2020)
Introduction: bullying is the manifestation of some form of intentional violence by one or more peers against another to cause pain and suffering. It is unacceptable behavior in the classroom and is the leading cause of teenage suicide. Objective: describe school bullying in a sample of undergraduate dental students at the Universidad Antonio Nariño. Materials and methods: a cross-sectional, descriptive, observational study was conducted on a sample of 218 dental school students using a survey constructed whit five domains and 65 questions to identify prevalence and status of school bullying. Results: of the 218 students included in the study, 166 were female (76.15%); average age was 21.4 ± 4.9 years and the median age was 20 years. It was found that 35.8 were involved in false rumors or gossip, and 28.1% had some experience that caused depression. More than half of the students felt confident in teachers to seek support and likewise considered that the faculty did not have mechanisms for student support. It was also evident that more than 40% of the students considered that at the University they had evidence of abuse of power due to competition or supremacy. Conclusions: The most frequent form of bullying is strongly linked to the verbal and relational domain.